Historisasi Pendidik dari Masa ke Masa - Bahri, Saiful (Taallum: Jurnal Pendidikan Islam, 2017)
In the days of the Salaf scholars, the profession of teachers had a glorious position. However, in Indonesia, at the beginning after independence, the teaching profession was a despised profession and was not appreciated at all, but now teachers are getting a bit more glorious places. This is because teacher professionalism is more appreciated and teachers welfare is improved. Indeed, in the days of scholars salaf first, educators or teachers get a noble place, but when the new order shifted into perspective Oemar Bakri, now in the third Millennium era, the teacher returned to get a glorious place.